1990
DOI: 10.3133/ofr89618
|View full text |Cite
|
Sign up to set email alerts
|

Sediment-source data for four basins tributary to Lake Tahoe, California and Nevada; August 1983-June 1988

Abstract: ILLUSTRATIONS DEFINITION OF TERMS Water year: A water year is a 12-month period, October 1 through September 30, designated by the calendar year in which it ends. In this report, years are water years unless otherwise noted. Sea level: In this report "sea level" refers to the National Geodetic Vertical Datum of 1929 (NGVD of 1929) a geodetic datum derived from a general adjustment of the first-order level nets of both the United States and Canada, formerly called Sea Level Datum of 1929.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Sediment budget studies and sediment transport models have identified stream channel erosion in the Tahoe basin as a major source of SS load (Hill et al. , 1990; Nolan and Hill, 1991; Simon et al.…”
Section: Resultsmentioning
confidence: 99%
“…Sediment budget studies and sediment transport models have identified stream channel erosion in the Tahoe basin as a major source of SS load (Hill et al. , 1990; Nolan and Hill, 1991; Simon et al.…”
Section: Resultsmentioning
confidence: 99%
“…A large amount of useful data on flow, suspended sediment, and channel characteristics were available from previous studies conducted in the Lake Tahoe Basin (Jorgensen et al. , 1978; Hill et al. , 1990; Nolan and Hill, 1991; Rowe et al.…”
Section: Research Approachmentioning
confidence: 99%
“…Cross sections on Blackwood, General, Logan House, and Edgewood creeks were monumented with metal fence posts and labeled with brass plates (Hill et al. , 1990) by the USGS in 1983 and 1984.…”
Section: Estimates Of Fine‐sediment Contributions From Streambank Eromentioning
confidence: 99%
See 2 more Smart Citations